“Exploring findings from the Learning Without Borders Project: developing and supporting transnational academic leaders to enable TNE teaching excellence and internationalization of the curriculum” - Giridharan, Beena; Goerke, Veronica; Mazzolini, Margaret; Yeo, Shelley; Ling, Peter; Lueckenhausen, Gillian (AIEC, 2012)
Transnational education (TNE) involves collaborative efforts of programme and unit coordinators working with colleagues from offshore branch campuses or international partner institutions within cross-cultural contexts. Sustainable approaches to recognising and rewarding leaders in TNE are arguably key to achieving teaching excellence at partner and branch campuses. This conference session will explore perspectives of staff at both onshore and offshore campuses, as studied during a two-year collaborative project between the Australian and Malaysian campuses of Swinburne University of Technology and Curtin University. It will highlight the broad outcomes and recommendations from this Australian Learning and Teaching (ALTC, now Office for Learning & Teaching, OLT) funded project entitled “Learning Without Borders: Linking Development of transnational leadership roles to international and cross-cultural teaching excellence”.